Therapeutic Presence in Videoconferencing Psychotherapy: Therapist Experiences of Connecting Across the Digital Divide - Mulder, Justin (Université d'Ottawa / University of Ottawa, 2025)
Telepsychology has become increasingly prevalent, primarily due to the COVID-19 pandemic (Madigan et al., 2021), shifting psychotherapy from physical face-to-face settings to screen-based formats. This drastic change inevitably produced varied perspectives on telepsychology and raised numerous questions regarding best practices (Connolly et al., 2020). Online therapeutic presence is one such area necessitating greater exploration. While research supports therapists bringing their whole self into session to foster deep connections with their client on multiple levels (Geller & Greenberg, 2023), less is known about applying such models online. Therefore, this study focuses on understanding therapist perspectives on therapeutic presence within telepsychology. Two research questions guided this study: (1) what are psychotherapists' experiences of therapeutic presence throughout videoconferencing psychotherapy sessions? and (2) how do psychotherapists overcome the challenges and barriers in videoconferencing psychotherapy? A semi-structured interview protocol was used to gather qualitative data from ten experienced therapists through 45-60-minute interviews. Braun and Clarke's (2021) six-step reflexive thematic analysis was used to analyse the data. Six main themes and 12 subthemes emerged through the data analysis. The study's findings support therapeutic presence's relevance in VC therapy, lending credence to the common factor hypothesis (Geller & Greenberg, 2023). Yet, some therapists felt less connected with certain clients online, indicating that the medium of VC psychotherapy may not appeal to all equally. Most reported barriers and challenges aligned with past research (Batastini et al., 2020), were surmountable, and did not greatly impact therapeutic presence.
Keywords: Telepsychology; Therapeutic presence; Videoconferencing psychotherapy; Thematic analysis